Role of Wnt signaling pathway in joint development and cartilage degeneration - Li, Xinyan; Han, Yuanyuan; Li, Guimiao; Zhang, Yingze; Wang, Juan; Feng, Chen (Frontiers in Cell and Developmental Biology, 2023)
Osteoarthritis (OA) is a prevalent musculoskeletal disease that affects approximately 500 million people worldwide. Unfortunately, there is currently no effective treatment available to stop or delay the degenerative progression of joint disease. Wnt signaling pathways play fundamental roles in the regulation of growth, development, and homeostasis of articular cartilage. This review aims to summarize the role of Wnt pathways in joint development during embryonic stages and in cartilage maintenance throughout adult life. Specifically, we focus on aberrant mechanical loading and inflammation as major players in OA progression. Excessive mechanical load activates Wnt pathway in chondrocytes, resulting in chondrocyte apoptosis, matrix destruction and other osteoarthritis-related changes. Additionally, we discuss emerging Wnt-related modulators and present an overview of emerging treatments of OA targeting Wnt signaling. Ultimately, this review provides valuable insights towards discovering new drugs or gene therapies targeting Wnt signaling pathway for diagnosing and treating osteoarthritis and other degenerative joint diseases.